Managerial skills and institutional capacity for municipal service delivery - Marais Luni (University of the Free State, 2003)
English: Since the early nineteen nineties a number of social and political changes emanated from the transformation process in South Africa. These changes had an effect on all spheres of government. The local sphere of government has particularly been affected by the changes since it is the sphere closest to the people and directly responsible for municipal service delivery. The Constitution of the Republic of South Africa, 1996 (Act 108 of 1996) has furthermore outlined values and principles for public officials to comply with, pertaining to service delivery to inhabitants. It is therefore necessary to have skilled and competent public officials in order to comply with constitutional requirements. The purpose of the study is to identify and analyse the status and relevance of managerial skills in the local sphere of government as well as its influence on municipal service delivery. Managers in municipalities should exhibit particular skills and competencies in order to fulfil their developmental role and provide quality municipal services to inhabitants. The study focuses specifically on the Nokeng Tsa Taemane Municipality which is categorised as a category B municipality in terms of the Constitution of the Republic of South Africa, 1996 (Act 108 of 1996). The government of South Africa has promulgated legislation and official policies to assist managers in municipalities pertaining to their roles, functions and responsibilities towards municipal service delivery. Managers in the local sphere of government are compelled to implement the legislative directives in order to improve the effectiveness and efficiency of municipal service delivery and to fulfil their mandate. This study furthermore investigates the institutional capacity in the Nokeng Tsa Taemane Municipality as well as its influence on municipal service delivery. The institutional capacity of a municipality should support managers in the exercising of their duties. It investigates the ability of the necessary resources, systems, procedures and managerial tools at the municipality in order to determine whether it could provide adequate support to managers. It became evident that the majority of systems and procedures at the municipality are not in place or not used to its fullest potential, which reflects on the substantial lack of institutional capacity. Not only are inadequate human resources a restricting factor to municipal service delivery, but financial impediments are the single most important obstacle to the delivery of municipal services of quality. The government of South Africa has furthermore committed itself to the improvement of the skills levels of public officials and to establish a culture of learning in the public service. For these purposes legislation and policies pertaining to skills development and training have also been promulgated. This study outlines the various legislative requirements pertaining to skills development and training, and furthermore make recommendations in this regard. It became evident that managers of the Nokeng Tsa Taemane Municipality, especially on middle management level do not possess the required skills and competencies to provide quality municipal services to inhabitants. It is therefore recommended that municipalities should make use of training opportunities for senior and middle managers to improve the skills levels of managers. The Nokeng Tsa Taemane Municipality should in conclusion make it a priority to improve not only its managerial skills, but also the institutional capacity of the municipality. It is imperative for the municipality to increase its revenue-base as a means to improve the financial situation of the municipality which could result in the eventual improvement of municipal service delivery.

Afrikaans: Verskeie maatskaplike en politieke veranderings het vanaf die vroeë negentien negentigs voortgespruit uit die transformasieproses in Suid-Afrika. Hierdie veranderings het In invloed gehad op alle regeringssfere. Die plaaslike regeringssfere veral, is deur die veranderings beïnvloed aangesien dit die sfeer naaste aan die gemeenskap en direk verantwoordelik vir munisipale dienslewering is. Voorts skets die Grondwet van die Republiek van Suid-Afrika, 1996 (Wet 108 van 1996) die waardes en beginsels waaraan openbare amptenare moet voldoen met betrekking tot dienslewering aan inwoners. Dit is daarom noodsaaklik om bekwame en bevoegde openbare amptenare te hê om te voldoen aan grondwetlike vereistes. Die doel van die studie is om die status en toepaslikheid van bestuursvaardighede in die plaaslike regeringssfere te identifiseer en te analiseer, asook die invloed daarvan op munisipale dienslewering. Bestuurders in munisipaliteite behoort bepaalde vaardighede en bevoegdhede aan die dag te lê ten einde hulle ontwikkelingsrol te vervul en kwaliteit munisipale dienste aan inwoners te lewer. Die studie fokus spesifiek op die Nokeng Tsa Taemane Munisipaliteit wat ingevolge die Grondwet van die Republiek van Suid-Afrika, 1996 (Wet 108 van 1996) as In kategorie B munisipaliteit gekategoriseer word. Die regering van Suid-Afrika het wetgewing en amptelike beleid gepromulgeer ten einde bystand te verleen aan bestuurders van munisipaliteite met betrekking tot hulle rolle, funksies en verantwoordelikhede ten opsigte van munisipale dienslewering. Bestuurners in die plaaslike regeringsfere is genoodsaak om wetgewende instruksies te implimenteer ten einde die effektiwiteit en doeltreffendheid van munisipale dienslewering te verbeter en hulle mandaat te vervul. Voorts ondersoek die studie die institusionele bevoegdheid van die Nokeng Tsa Taemane Munisipaliteit, asook die invloed daarvan op munisipale dienslewering. Die institusionele bevoegdheid van In munisipaliteit behoort ondersteuning aan bestuurders in die uitvoer van hulle pligte te bied. Die vermoë van die nodige hulpbronne, stelsels, prosedures en bestuursgereedskap in die munisipaliteit word ondersoek ten einde vas te stelof dit voldoende ondersteuning aan bestuurders bied. Dit is duidelik dat die meerderheid stelsels en prosedures by die munisipaliteit nie in plek is nie of nie tot die volle potensiaal benut word nie, wat dui op die aansienlike tekort aan institusionele bevoegdheid. Nie net is onvoldoende menslike hulpbronne In beperkende faktor tot munisipale dienslewering nie, maar finansiële tekorte is die enkel mees belangrike struikelblok tot die lewering van kwaliteit munisipale dienste. Die regering van Suid-Afrika het hulleself toevertrou met die taak om die vaardigheidsvlakke van openbare amptenare te verbeter en In kultuur van leer in die staatsdiens daar te stel. Vir hierdie doeleindes is wetgewing en beleid met betrekking tot vaardigheidsontwikkeling en opleiding ook gepromulgeer. Die studie skets die verskeie wetgewende vereistes met betrekking tot vaardigheidsontwikkeling en opleiding en maak voorts aanbevelings in hierdie verband. Dit is duidelik dat bestuurders van die Nokeng Tsa Taemane Munisipaliteit, veral op middelvlakbestuur, nie oor die vereiste vaardighede en bevoegdhede beskik om kwaliteit munisipale dienste aan inwoners te lewer nie. Daarom word dit aanbeveel dat munisipaliteite gebruik behoort te maak van opleidingsgeleenthede vir senior en middelvlakbestuur om die vaardigheidsvlakke van bestuurders te verhoog. Dit moet gevolglik vir die Nokeng Tsa Taemane Munisipaliteit prioriteit wees om om nie net bestuursvaardighede nie, maar ook die institusionele bevoegdheid van die munisipaliteit te verbeter. Dit is noodsaaklik dat die munisipaliteit sy inkomstebasis vergroot as 'n middel tot die verbetering van die finansiële situasie van die munisipaliteit, wat die uiteindelike verbetering van munisipale dienslewering tot gevolg kan hê.
Keywords: Managerial skills; Institutional capacity; Municipal service delivery; Municipality; Local government; Sustainable; Development; Municipal services -- South Africa -- Pretoria; Benchmarking (Management) -- South Africa -- Pretoria; Local government -- South Africa -- Pretoria; Personnel management; Dissertation ( (M.Pub. (Public Management))--University of the Free State, 2003